Microstructure regulation of CsxWO3 nanoparticles by organic acid for improved transparent thermal insulation performance. (January 2019) - Ran, Shuai; Liu, Jingxiao; Shi, Fei; Fan, Chuanyan; Yang, Jingyuan; Chen, Bin; Liu, Su-Hua
Graphical abstract: Highlights: Controllable synthesis of Csx WO3 were conducted using organic acid as deoxidizer. Tartaric acid exhibits the best reducibility in the synthesis of Csx WO3 . The reduction mechanism of different organic acid for generating W 5+ was studied. Csx WO3 formed with oxalic acid after annealing has the best visible transmission. Abstract: In order to further improve the transparent thermal insulation of Csx WO3, controllable synthesis of Csx WO3 nanoparticles from cheap and environment-friendly Na2 WO4 ·2H2 O and Cs2 SO4 by solvothermal method was conducted using different organic acids as reducing agents. The reducibility and reduction mechanisms of citric acid, tartaric acid and oxalic acid were investigated. It has been confirmed that tartaric acid has the strongest reducibility, and could produce the most W 5+ and oxygen vacancies in the Csx WO3 products before heat-treatment. The Csx WO3 nanoparticles synthesized with oxalic acid after heat-treatment exhibited the best crystallinity and the visible light transmission was about 10% higher than that of tartaric acid and citric acid. It is significant for the low-cost production of Csx WO3 nanoparticles with higher transparent thermal insulation performance.